The childhood place in fashion editorials: an analysis on the adultization of children in the consumer society - Oliveira, Marta Regina Furlan de; Silva, Larissa Delgado Bueno da; Paschoal, Jaqueline Delgado (Universidade Estadual Paulista, Faculdade de Ciências e Letras de Araraquara, 2020)
This study had the purpose of critically analyzing the conceptions of children in the fashion editorials, as well as assessing whether they can contribute to the early development of “adultization” of the infant consumer. It is believed that the discourse of children's fashion editorials dictates standards of beauty and behaviors similar to the adult world, especially in relation to clothing, accessories, aesthetic standards and means of consumption. In addition, the advertising industry does not always consider children's particularities when selling its products, thus contributing to the process of adultization of children. The methodology used was bibliographic research and documentary research in the light of the foundations of Critical Theory and of authors who dialogue with this theoretical perspective. The results of the research indicate that the major brands, especially those aimed at children, induce children into environments and situations of adult domain, as well as the means of consumption. Therefore, the importance of the family and the school as spaces for reflection and combat in the cultural industry.